What was the Copper Age Clay Wagon Model of Budakalász (Hungary)? - Makkay, János (1963)
ersch. 1965; The clay wagon and chariot models from Mesopotamia: A systématisation and parallels from Hungary, South and Central Europe. Wagons as emblems of the divinity. Wagon models are not a replacement of a wagon burial. The use of wagon models as divinity emblems originated in Mesopotamia.